Functional outcome of intertan nailing in intertrochanteric fractures: a retrospective study utilizing Oxford hip score - S. S., Varun Roheet; E. R., Mithun; S. , Muthukumar (International Journal of Research in Orthopaedics, 2024)
Background: This study evaluates the functional outcome of intertan nailing in intertrochanteric fractures in terms of the Oxford Hip Score (OHS). Methods: Twenty-eight patients (10 males, 18 females, mean age: 75.2 years, range: 60-94 years) were analyzed. Mean follow-up period was 6 months (3–8 months) and 5 patients were lost to follow-up. Results: The overall average OHS was 37.2, with scores varying from 22 to 47. Nine patients had OHS scores above 40, indicating satisfactory function, while 10 patients scored between 30-39, denoting mild loss of function. Four patients had OHS scores of 20–29, indicating a moderate to severe loss of function. Conclusions: These findings indicate the varied functional outcomes of intertan nailing in intertrochanteric fractures and highlight the importance of individualized treatment strategies.